Prevalence and Risk Factors of Obesity among School Children in Sylhet, Bangladesh - Saha, Madhusudan; Adhikary, Dipal Krishna; Parvin, Irin; Sharma, Yuba Raj; Akhter, Fahmida; Majumder, Monojit (Journal of Nepal Health Research Council, 2018)
Background: Childhood obesity is found in affluent society, less physical activity and changes in food pattern. This study was designed to see prevalence and risk factors of childhood obesity among school children of Sylhet city. Methods: Students of class five and six of two schools of Sylhet city were randomly selected. Demographic and anthropometric data were collected and recorded in predesigned data sheet. BMI and percentile were calculated using official centre for disease control growth chart for 2 to 20 years. Logistic regression analysis was done to see association of various factors with childhood obesity. P value of ≤0.05 was taken as significant. Results: Total 288 children were included in this study. Age varied from 10 to 14 years. Among them 5.6% and 8.7% were found to be obese and overweight respectively. Obesity was significantly higher among girls (6.8% vs3.6%). Prevalence of obesity and overweight (p=0.001) was more among those who spent less time in physical exercise and outdoor games. Food habit, television watching, computer gaming and duration of sleep were not found as significant predictor of obesity. Conclusions: Obesity was significantly higher among girls (6.8% vs3.6%). Girls with less physical activity were mainly associated with overweight and obesity.